2014
DOI: 10.1016/j.envres.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to traffic pollution, acute inflammation and autonomic response in a panel of car commuters

Abstract: Background Exposure to traffic pollution has been linked to numerous adverse health endpoints. Despite this, limited data examining traffic exposures during realistic commutes and acute response exists. Objectives: We conducted the Atlanta Commuters Exposures (ACE-1) Study, an extensive panel-based exposure and health study, to measure chemically-resolved in-vehicle exposures and corresponding changes in acute oxidative stress, lipid peroxidation, pulmonary and systemic inflammation and autonomic response. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 44 publications
6
59
0
2
Order By: Relevance
“…Although some studies have explored the acute effects of short-term exposure to traffic emission on pulmonary function in real-world settings, the results were inconsistent. Some indicated negative effects [16][17][18][19], while others reported no acute influence [20][21][22][23]. In addition, some positive associations between traffic exposure during cycling and pulmonary function were found [24,25].…”
Section: Introductionmentioning
confidence: 86%
“…Although some studies have explored the acute effects of short-term exposure to traffic emission on pulmonary function in real-world settings, the results were inconsistent. Some indicated negative effects [16][17][18][19], while others reported no acute influence [20][21][22][23]. In addition, some positive associations between traffic exposure during cycling and pulmonary function were found [24,25].…”
Section: Introductionmentioning
confidence: 86%
“…Other studies also indicate that sudden increase or decrease of exposure to air pollution may affect asthmatic symptoms or emergency department visits (136)(137)(138). Indeed, a decrease in the number of acute asthma events of over 40% was found after reduction in air pollution during summer Olympic games (138).…”
Section: Pollutionmentioning
confidence: 99%
“…Because traffic emissions are a major source of pollutants, peak concentrations tend to occur near or on roads, which is where an individual may receive a disproportionately large fraction of their total daily personal exposures. Indeed studies have reported elevated risks for developing asthma and reduced lung function in children living near to heavily-trafficked roads (Brugge et al , 2007), as well as measured changes in cardiac biomarkers and pulmonary function in adults driving or working in private vehicles (cars) (Riediker et al , 2004; Heinrich et al , 2005; Sarnat et al , 2014). …”
Section: Introductionmentioning
confidence: 99%